2011
DOI: 10.1038/onc.2011.241
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage formation of an epigenetic field defect in a mouse colitis model, and non-essential roles of T- and B-cells in DNA methylation induction

Abstract: Epigenetic fields for cancerization are involved in development of human cancers, especially those associated with inflammation and multiple occurrences. However, it is still unclear when such field defects are formed and what component of inflammation is involved in induction of aberrant DNA methylation. Here, in a mouse colitis model induced by dextran sulfate sodium (DSS), we identified three CpG islands specifically methylated in colonic epithelial cells exposed to colitis. Their methylation levels started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…Increased production of NO in vitro is reported to increase the enzyme activity of DNA methyltransferases without changing their expression, and to induce DNA methylation of specific genes (52). In the human and gerbil stomachs infected by H. pylori and mouse colons treated with DSS, no changes in the expression of DNA methyltransferases 1, 3a, and 3b were observed (28,45,49). It is possible that a signal from chronic inflammation, possibly IL1b, and elevation of NO in epithelial cells lead to inappropriate localization of deregulated DNA methyltransferase(s) to methylation-susceptible CpG islands (see below) and induce aberrant DNA methylation as an infrequent event.…”
Section: Critical Roles Of Specific Types Of Inflammation In Methylatmentioning
confidence: 99%
“…Increased production of NO in vitro is reported to increase the enzyme activity of DNA methyltransferases without changing their expression, and to induce DNA methylation of specific genes (52). In the human and gerbil stomachs infected by H. pylori and mouse colons treated with DSS, no changes in the expression of DNA methyltransferases 1, 3a, and 3b were observed (28,45,49). It is possible that a signal from chronic inflammation, possibly IL1b, and elevation of NO in epithelial cells lead to inappropriate localization of deregulated DNA methyltransferase(s) to methylation-susceptible CpG islands (see below) and induce aberrant DNA methylation as an infrequent event.…”
Section: Critical Roles Of Specific Types Of Inflammation In Methylatmentioning
confidence: 99%
“…We read with great interest the recent article by Katsurano et al [1] describing a mouse colitis model leading to tumor formation. They report that an epigenetic field defect forms early after treatment with dextran sulfate sodium (DSS) and that the epigenetic alterations continue to increase even with diminishing stimulation.…”
Section: Commentary On Hot Topicsmentioning
confidence: 99%
“…In addition to epigenetic alteration of expression of miRNAs, other common types of epigenetic alterations in cancers that change gene expression levels include direct hypermethylation or hypomethlyation of CpG islands of protein-encoding genes and alterations in histones and chromosomal architecture that influence gene expression [10,11] . The specific epigenetic alterations studied by Katsurano et al [1] , as well as epigenetic field defects in general, can be placed in a broad explanatory framework starting with the occurrence of DNA damage, a major primary event in progression to cancer as shown in Figure 1. In Figure 1 italicized capitalized abbreviations are symbols of epigenetically altered genes.…”
Section: Commentary On Hot Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…While a few initial studies have suggested aberrant methylation patterns in mouse models of IBD (14,15), both the effect of inflammation on DNA methylation and the functional outcome have not been investigated in detail yet. We have now used whole-genome bisulfite sequencing (16) to characterize the methylomes of the AOM/DSS mouse model at single-base resolution.…”
Section: Introductionmentioning
confidence: 99%